The Mystery of a Hansom Cab as Spatial Artefact: Exploring Class and the Spatial Unconscious in Nineteenth-Century Australia's Favourite Whodunnit. - Heino, Brett; Jackson, Luke C. (Australian Literary Studies, 2024)
Fergus Hume's The Mystery of a Hansom Cab has long been celebrated for its portrayal of the spaces and places of late-nineteenth century Melbourne. In this article, we seek to interrogate the relationship between the spatiality of Hume's Melbourne and social class. In particular, we employ a theoretical framework that combines structural Marxist literary analysis with the work of radical geographers, unified in the concept of a text's spatial unconscious. We argue that the spatial unconscious of The Mystery of a Hansom Cab registers the impact of middle-class liberal ideology on the representation of the spaces and places of the working-class and bourgeoisie. Putting this ideology to work, Hume attempts to create a literary world in which these spaces and places are radically differentiated and strictly balkanised. However, a close reading reveals flows, or porosities, of people and capital between these locations, porosities that indicate the limits of middle-class liberal ideology and the capacity of capital to produce abstract space.